Ruthenium(II) and Osmium(II) vinyl complexes as highly sensitive and selective chromogenic and fluorogenic probes for the sensing of carbon monoxide in air - Wilton-Ely,JD; Toscani,A; Brown,N; Dingwall,P; White,A; Marin-Hernandez,C; Moragues,M; Sancenon,F; Martinez-Manez,R (Chemistry - A European Journal, 2015)
The detection of carbon monoxide in solution and air has been achieved using simple, inexpensive systems based on the vinyl complexes [M(CH[DOUBLE BOND]CHR)Cl(CO)(BTD)(PPh3)2] (R=aryl, BTD=2,1,3-benzothiadiazole). Depending on the nature of the vinyl group, chromogenic and fluorogenic responses signalled the presence of this odourless, tasteless, invisible, and toxic gas. Solutions of the complexes in CHCl3 underwent rapid change between easily differentiated colours when exposed to air samples containing CO. More significantly, the adsorption of the complexes on silica produced colorimetric probes for the naked-eye detection of CO in the gas phase. Structural data for key species before and after the addition of CO were obtained by means of single X-ray diffraction studies. In all cases, the ruthenium and osmium vinyl complexes studied showed a highly selective response to CO with exceptionally low detection limits. Naked-eye detection of CO at concentrations as low as 5ppb in air was achieved with the onset of toxic levels (i.e., 100ppm), thus resulting in a remarkably clear colour change. Moreover, complexes bearing pyrenyl, naphthyl, and phenanthrenyl moieties were fluorescent, and greater sensitivities were achieved (through turn-on emission fluorescence) in the presence of CO both in solution and air. This behaviour was explored computationally using time-dependent density functional theory (TDDFT) experiments. In addition, the systems were shown to be selective for CO over all other gases tested, including water vapour and common organic solvents. Supporting the metal complexes on cellulose strips for use in an existing optoelectronic device allows numerical readings for the CO concentration to be obtained and provision of an alarm system.